Project decisions : the art and science - Virine, Lev, 1964-; Trumper, Michael, 1963- (Berrett-Koehler Publishers, 2019)
An entertaining and easy-to-read guide to a structured project decision-making process, this practical book will help you identify risks and perform basic quantitative and qualitative risk and decision analyses. --